2017
DOI: 10.5194/acp-2017-942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gas phase composition and secondary organic aerosol formation from gasoline direct injection vehicles investigated in batch and flow reactors: effects of prototype gasoline particle filters

Abstract: Abstract. Gasoline direct injection (GDI) vehicles have recently been identified as a significant source of carbonaceous aerosol, of both primary and secondary origin. Here we investigated primary emissions and secondary organic aerosol (SOA) formation from GDI vehicle exhaust for multiple vehicles and driving test cycles, and novel GDI after-treatment systems.Emissions were characterized by proton transfer reaction time-of-flight mass spectrometry (gaseous non-methane organic 15 compounds, NMOCs), aerosol … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In this study, we investigated the SOA production from two current GDI vehicles with and without a catalyzed GPF. To the best of our knowledge, only Pieber et al 36 evaluated SOA production from GDI vehicles equipped with prototype GPFs using a batch and a flow reactor. While the authors did not find differences in SOA formation with the tested noncatalyzed and catalytically coated GPFs, they suggested that the catalyzed GPFs could be installed at the same position as the underfloor TWC, and that this should be investigated in future work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, we investigated the SOA production from two current GDI vehicles with and without a catalyzed GPF. To the best of our knowledge, only Pieber et al 36 evaluated SOA production from GDI vehicles equipped with prototype GPFs using a batch and a flow reactor. While the authors did not find differences in SOA formation with the tested noncatalyzed and catalytically coated GPFs, they suggested that the catalyzed GPFs could be installed at the same position as the underfloor TWC, and that this should be investigated in future work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Single-ring aromatics are traditionally thought to be the most important secondary organic aerosol (SOA) precursors from combustion emissions. While this has been shown to be the case for some emissions, e.g., from twostroke engines (Platt et al, 2014), in other cases nontraditional precursors were assessed to be responsible for the bulk of the SOA mass formed, e.g., for biomass smoke (Bruns et al, 2016) or on-road vehicles (Platt et al, 2013(Platt et al, , 2017Pieber et al, 2017). Similar to these emissions, aging of aircraft emissions studied by Miracolo et al (2011Miracolo et al ( , 2012 in a smog chamber produced substantial amounts of secondary PM exceeding primary PM emissions severalfold.…”
Section: Kılıç Et Al: Identification Of Secondary Aerosol Precursorsmentioning
confidence: 99%
“…Single-ring aromatics, such as xylenes, methylbenzenes, toluene, and benzene, were previously linked with SOA formation (e.g., Odum et al, 1997;Ng et al, 2007). These aromatic gases are important contributors in the emissions from combustion sources such as two-stroke scooters (Platt et al, 2013) or wood burning (Bruns et al, 2016). Idling exhaust contained 20 % (mass weighted) of aromatic HCs.…”
Section: Precursor Gases Of Soa: Idlingmentioning
confidence: 99%
“…Single-ring aromatics, such as xylenes, methylbenzenes, toluene, and benzene, were previously linked with SOA formation (e.g., Odum et al, 1997;Ng et al, 2007). These aromatic gases are important contributors in the emissions from combustion sources such as two-stroke scooters (Platt et al, 2013) or wood burning . Idling exhaust contained 20 % (mass weighted) of aromatic HCs.…”
Section: Precursor Gases Of Soa: Idlingmentioning
confidence: 99%
“…Single-ring aromatics are traditionally thought to be the most important secondary organic aerosol (SOA) precursors from combustion emissions. While this has been shown to be the case for some emissions, e.g., from twostroke engines (Platt et al, 2014), in other cases nontraditional precursors were assessed to be responsible for the bulk of the SOA mass formed, e.g., for biomass smoke or on-road vehicles (Platt et al, 2013Pieber et al, 2017). Similar to these emissions, aging of aircraft emissions studied by Miracolo et al (2011Miracolo et al ( , 2012 in a smog chamber produced substantial amounts of secondary PM exceeding primary PM emissions severalfold.…”
Section: Introductionmentioning
confidence: 99%